The Effect of Downvotes on Content Creation: Evidence from Social Media - Deolankar, Varad; Fong, Jessica; Sriram, S. (Journal of Marketing Research, 2026)
This article studies how receiving negative peer feedback, in the form of downvotes, affects user-generated content creation on Reddit. The authors focus on the following outcomes: (1) propensity to post (incidence), (2) where users post, and (3) the strength of opinion (intensity), measured by the extremity of users’ texts. The latter two outcomes are important given ongoing concerns about how social media platforms may contribute to echo chamber formation and polarization. The authors find that negative feedback, relative to no feedback, increases users’ subsequent posting activity, and they do not find evidence that receiving negative feedback drives users away, alleviating concerns about echo chamber formation. In addition, negative peer feedback moderates extreme sentiments—when initial views are extreme, users temper the intensity of their subsequent posts. These effects of negative feedback are consistent with users attempting to maintain their reputation.